Literature Review: Green Marketing Strategy and Green Hospital to Achieve Sustainable Competitive Advantage - Lestari, Marselli Widya; Sari, Suzanna Ratih; Arso, Septo Pawelas (Jurnal Medis Islam Internasional, 2022)
Background : The concept of green hospital and green marketing is still rarely applied to hospitals in Indonesia. Even though this strategy is a very good potential. In addition to playing a role in environmental conservation, hospitals can achieve Sustainable Competitive Advantage. Objective : The aim of this article is focused on green marketing and green hospital strategies and their role in increasing sustainable competitive advantage. Methods : This article is a literature review of 7 journals from several sources such as Google Scholar, SINTA Journal, and pubmed in the last 10 years. Result : The core concept of green hospitals focuses on the production and use of energy, water resources, the use of solar energy for electricity and reducing electricity use, good aeration, climatic features, green open spaces and the long-term impact of building materials. The concept plays a role in improving public health while reducing the environmental impact around it. Green marketing is one of the strategies that the hospital marketing team uses today as the key strategy for SCA. Conclusion : In the end, this concept has 2 goals, improving environmental quality and customer satisfaction. Thus, the implementation of green marketing into a marketing strategy can be the key in achieving sustainable competitive advantage in hospitals.